2013
DOI: 10.2168/lmcs-9(1:2)2013
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically almost all \lambda-terms are strongly normalizing

Abstract: Abstract. We present a quantitative analysis of various (syntactic and behavioral) properties of random λ-terms. Our main results show that asymptotically, almost all terms are strongly normalizing and that any fixed closed term almost never appears in a random term. Surprisingly, in combinatory logic (the translation of the λ-calculus into combinators), the result is exactly opposite. We show that almost all terms are not strongly normalizing. This is due to the fact that any fixed combinator almost always ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 22 publications
2
53
2
Order By: Relevance
“…The limit value (3.30), coinciding in the natural size notion with the corresponding mean for head abstractions (3.24), is close to 0.4196. This result stands, again, is sharp contrast to the canonical model of David et al [19] in which variables (in closed terms) tend to be arbitrarily far from their binding abstractions. Let us point out that such a disparity is a consequence of the different combinatorial models for λ-terms.…”
Section: De Bruijn Index Values In Plain Lambda Termscontrasting
confidence: 67%
See 1 more Smart Citation
“…The limit value (3.30), coinciding in the natural size notion with the corresponding mean for head abstractions (3.24), is close to 0.4196. This result stands, again, is sharp contrast to the canonical model of David et al [19] in which variables (in closed terms) tend to be arbitrarily far from their binding abstractions. Let us point out that such a disparity is a consequence of the different combinatorial models for λ-terms.…”
Section: De Bruijn Index Values In Plain Lambda Termscontrasting
confidence: 67%
“…This central difference of both combinatorial models leads to remarkably contrasting asymptotic properties, including normalisation of large random λ-terms, cf. [19,7,5].…”
Section: De Bruijn Index Values In Plain Lambda Termsmentioning
confidence: 99%
“…The to our knowledge first enumerative investigation of lambda terms was performed in [10]. Later, particular classes of lambda terms like linear and affine terms have been enumerated [4,25].…”
Section: Introductionmentioning
confidence: 99%
“…Representing a rather functional approach to logic and computations, lambda calculus was first studied by David et al (see [10]). Assuming a canonical representation of closed λ-terms, David et al showed that asymptotically almost all λ-terms are strongly normalising.…”
Section: Introductionmentioning
confidence: 99%